Using one way fluid structure interaction coupling to investigate the effect of blood flow on the bileaflet mechanical heart valve structure - Nasif, M.S. (Asian Research Publishing Network, 2016)
A numerical simulation investigation was conducted to investigate the effect of vibration on the structure of bileaflet mechanical heart valve by using one way Fluid Structure Interaction coupling technique. The forces generated due to blood flow and heart pulsation which consequently cause vibrations is investigated numerically. In this model, the heartbeat used is 120 BPM and the bileaflet heart valve leaflet angles where varied 25o, 63o and 85o. The results of the numerical simulation revealed that the blood velocity and von-Mises stress in the connection pin and valve housing at the angle 25o increased by up to 96 and 78 respectively as compared with the blood velocity and von-Mises stresses at fully open angle 85o. The results of the numerical simulation indicated the von Mises stresses values may reach higher values than the allowable stresses of the artificial heart valve especially at the pin connect and valve housing. This may result in the artificial heart valve failure, however, it depends on the valve leaflet position. Â©2006-2016 Asian Research Publishing Network (ARPN).